Modeling Bacterial Attachment Mechanisms on Superhydrophobic and Superhydrophilic Substrates - T. Brian Cavitt; Niyati Pathak (Pharmaceuticals, 2021)
Superhydrophilic and superhydrophobic substrates are widely known to inhibit the attachment of a variety of motile and/or nonmotile bacteria. However, the thermodynamics of attachment are complex. Surface energy measurements alone do not address the complexities of colloidal (i.e., bacterial) dispersions but do affirm that polar (acid-base) interactions (<semantics>ΔGAB</semantics>) are often more significant than nonpolar (Lifshitz-van der Waals) interactions (<semantics>ΔGLW</semantics>). Classical DLVO theory alone also fails to address all colloidal interactions present in bacterial dispersions such as <semantics>ΔGAB</semantics> and Born repulsion (<semantics>ΔGBorn</semantics>) yet accounts for the significant electrostatic double layer repulsion (<semantics>ΔGEL</semantics>). We purpose to model both motile (e.g., P. aeruginosa and E. coli) and nonmotile (e.g., S. aureus and S. epidermidis) bacterial attachment to both superhydrophilic and superhydrophobic substrates via surface energies and extended DLVO theory corrected for bacterial geometries. We used extended DLVO theory and surface energy analyses to characterize the following Gibbs interaction energies for the bacteria with superhydrophobic and superhydrophilic substrates: <semantics>ΔGLW</semantics>, <semantics>ΔGAB</semantics>, <semantics>ΔGEL</semantics>, and <semantics>ΔGBorn</semantics>. The combination of the aforementioned interactions yields the total Gibbs interaction energy (<semantics>ΔGtot</semantics>) of each bacterium with each substrate. Analysis of the interaction energies with respect to the distance of approach yielded an equilibrium distance (<semantics>deq</semantics>) that seems to be independent of both bacterial species and substrate. Utilizing both <semantics>deq</semantics> and Gibbs interaction energies, substrates could be designed to inhibit bacterial attachment.